PROBLEMS OF PSYCHOLOGY IN THE CHARACTER OF A PERSON - Burkhanova Dilnoza (Galaxy International Interdisciplinary Research Journal, 2022)
The traits of human character are revealed. Types of character are classified, the role of character in personality development is discussed. The personal qualities of a person are revealed: kindness, courage, responsibility, determination, perseverance, reliability, honesty, they help a person achieve success in life.